Cerebrospinal Fluid YKL-40 and Chitotriosidase Levels in Frontotemporal Dementia Vary by Clinical, Genetic and Pathological Subtype - Woollacott, Ione O.C. (Dement Geriatr Cogn Disord, 2020)
BACKGROUND: Chronic glial dysfunction may contribute to the pathogenesis of frontotemporal dementia (FTD). Cerebrospinal fluid (CSF) levels of glia-derived proteins YKL-40 and chitotriosidase are increased in Alzheimer's disease (AD) but have not been explored in detail across the spectrum of FTD. METHODS: We investigated whether CSF YKL-40 and chitotriosidase levels differed between FTD patients and controls, across different clinical and genetic subtypes of FTD, and between individuals with a clinical FTD syndrome due to AD versus non-AD (frontotemporal lobar degeneration, FTLD) pathology (based on CSF neurodegenerative biomarkers). Eighteen healthy controls and 64 people with FTD (behavioural variant FTD, n = 20; primary progressive aphasia [PPA], n = 44: nfvPPA, n = 16, svPPA, n = 11, lvPPA, n = 14, PPA-NOS, n = 3) were included. 10/64 had familial FTD, with mutations in GRN(n = 3), MAPT(n = 4), or C9orf72 (n = 3). 15/64 had neurodegenerative biomarkers consistent with AD pathology. Levels were measured by immunoassay and compared using multiple linear regressions. We also examined relationships of YKL-40 and chitotriosidase with CSF total tau (T-tau), phosphorylated tau 181 (P-tau) and β-amyloid 1–42 (Aβ42), with each other, and with age and disease duration. RESULTS: CSF YKL-40 and chitotriosidase levels were higher in FTD, particularly lvPPA (both) and nfvPPA (YKL-40), compared with controls. GRN mutation carriers had higher levels of both proteins than controls and C9orf72 expansion carriers, and YKL-40 was higher in MAPT mutation carriers than controls. Individuals with underlying AD pathology had higher YKL-40 and chitotriosidase levels than both controls and those with likely FTLD pathology. CSF YKL-40 and chitotriosidase levels were variably associated with levels of T-tau, P-tau and Aβ42, and with each other, depending on clinical syndrome and underlying pathology. CSF YKL-40 but not chitotriosidase was associated with age, but not disease duration. CONCLUSION: CSF YKL-40 and chitotriosidase levels are increased in individuals with clinical FTD syndromes, particularly due to AD pathology. In a preliminary analysis of genetic groups, levels of both proteins are found to be highly elevated in FTD due to GRN mutations, while YKL-40 is increased in individuals with MAPT mutations. As glia-derived protein levels generally correlate with T-tau and P-tau levels, they may reflect the glial response to neurodegeneration in FTLD.